Ответ:
1) х=4
2) х=28
3) х=1
4)
Пошаговое объяснение:
<> - знак неравенства
1) x+4 <>0; x<> -4
![\frac{x^{2} -16}{x+4} =\frac{(x-4)(x+4)}{x+4} =x-4=0 \frac{x^{2} -16}{x+4} =\frac{(x-4)(x+4)}{x+4} =x-4=0](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B2%7D%20-16%7D%7Bx%2B4%7D%20%3D%5Cfrac%7B%28x-4%29%28x%2B4%29%7D%7Bx%2B4%7D%20%3Dx-4%3D0)
x=4
2) ![\frac{5}{x+7} -\frac{3}{x-7}=0 \frac{5}{x+7} -\frac{3}{x-7}=0](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7Bx%2B7%7D%20-%5Cfrac%7B3%7D%7Bx-7%7D%3D0)
x<>7; х<> -7
домножим обе части на (х-7)(х+7)
получим следующее:
5(х-7)-3(х+7)=0
5х-35-3х-21=2х-56=0
2х=56
х=28
3) ![\frac{9x-7}{3x-2}-\frac{4x-5}{2x-3}=1 \frac{9x-7}{3x-2}-\frac{4x-5}{2x-3}=1](https://tex.z-dn.net/?f=%5Cfrac%7B9x-7%7D%7B3x-2%7D-%5Cfrac%7B4x-5%7D%7B2x-3%7D%3D1)
3x-2<>0
2x-3<>0
x<>2/3; x<>3/2
домножим обе части на (3x-2)(2х-3)
получим следующее:
(9x-7)(2x-3)-(4x-5)(3x-2)=(3x-2)(2х-3)
раскроем скобки
18х²-41х+21-12х²+23х-10=6х²-13х+6
-5х+5=0
5х=5
х=1
4)